Improving Students' Speaking Skills Through the Use of the ROLEPLAYING Learning Model in Elementary School Students - Awalia Ramadani; Paldy Paldy; Haspidawati Nur (EDUJAVARE: International Journal of Educational Research, 2026)
Indonesian is a subject that plays an important role in developing students' language skills, including listening, speaking, reading, and writing. This study aims to improve students' speaking skills through the use of the Role Playing  learning model in grade IV students at SDN 42 Limpomajang, Palopo City. This type of research is class action research (PTK). The subjects in this study are grade IV students totaling 10 students. The research instruments used were speech skills performance tests, observation of learning implementation, and observation of student activities. The data analysis technique used is descriptive quantitative. The results of the study showed that the average test score on students' speaking skills increased through the use of the role playing  learning model in grade IV of SDN 42 Limpomajang, Palopo City, where the increase that occurred from cycle I to cycle II was 20%. This is evidenced by the results of the research where the first cycle obtained 60% of student learning outcomes and the second cycle obtained 80% of the learning outcomes. The learning implementation process showed an increase where the average value of the percentage of learning implementation was 91.25% (Very Good) in the first cycle to 100% (Very Good), which was accompanied by an increase in student activities to reach the very active category.